MEDI0382, a GLP‐1/glucagon receptor dual agonist, meets safety and tolerability endpoints in a single‐dose, healthy‐subject, randomized, Phase 1 study - Ambery, Philip D.; Klammt, Sebastian; Posch, Maximillian G.; Petrone, Marcella; Pu, Wenji; Rondinone, Cristina; Jermutus, Lutz; Hirshberg, Boaz (British journal of clinical pharmacology, 2018)
Aims MEDI0382 is a balanced glucagon‐like peptide‐1/glucagon receptor dual agonist under development for the treatment of type 2 diabetes mellitus and non‐alcoholic steatohepatitis. The primary objective was to assess the safety of MEDI0382 in healthy subjects. Methods In this placebo‐controlled, double‐blind, Phase 1 study, healthy subjects (aged 18–45 years) were randomized (3:1) to receive a single subcutaneous dose of MEDI0382 or placebo after ≥8 h of fasting. The study consisted of six cohorts that received study drug at 5 μg, 10 μg, 30 μg, 100 μg, 150 μg or 300 μg. The primary objective was safety and tolerability. Secondary endpoints included assessments of pharmacokinetics and immunogenicity. All subjects were followed for up to 28 days. Results A total of 36 subjects received MEDI0382 (n = 6 per cohort) and 12 subjects received placebo (n = 2 per cohort). Treatment‐emergent adverse events (TEAEs) occurred more frequently with MEDI0382 vs. placebo, which was mostly due to an increased occurrence at MEDI0382 doses ≥150 μg. All TEAEs were mild or moderate in severity. The most common TEAEs were vomiting, nausea and dizziness. There appeared to be a dose‐dependent increase in heart rate with MEDI0382 treatment. MEDI0382 showed linear pharmacokinetic profile (time to maximum plasma concentration: 4.50–9.00 h; elimination half‐life: 9.54–12.07 h). No immunogenicity was observed in the study. Conclusions In this single‐dose, Phase 1 study in healthy subjects, the safety and pharmacokinetic profiles of MEDI0382 support once‐daily dosing and further clinical development of MEDI0382.